DETERMINANTS OF ACCOUNTING PRECAUTION: An Empirical Study of Consumer Non-Cyclical Sector Companies in Indonesia - Dwi Haryanti, Christina; Mahameru Rosy Rochmatullah (ITB AAS Indonesia Surakarta, 2025)
This study aims to test and analyze the determinants of accounting prudence. The analysis is carried out by testing the influence of several indicators such as sales growth, capital intensity, and company size. Using a research sample of 42 companies in the consumer non cyclicals sector listed on the Indonesia Stock Exchange (IDX) in 2021-2023. This study analyzes several indicators using multiple linear regression. Based on the results of the tests that have been carried out, it shows that the variables of sales growth and capital intensity do not affect accounting prudence. While company size affects accounting prudence. While the moderating variables of sales growth with good corporate governance moderation, capital intensity with good corporate governance moderation show results that do not affect accounting prudence. While company size with good corporate governance moderation affects accounting prudence.